Brexit and invasive species: a case study of the cognitive and affective encoding of 'abject nature' in contemporary nationalist ideology. - Davies, Jonathan (Cultural Studies, 2022)
The article addresses the issue of invasive non-native species in Britain and its proximate cultural and political implications. Notably, it charts the co-option of this issue by sections of the nationalist press since the escalation of the European migrant crisis in 2015 and their strategic metaphorical alignment of human and extra-human migration, particularly in the period surrounding the Brexit referendum. These reports serve as the basis for a wider conjunctural analysis; assessing contemporary figurations of nature in nationalist ideology, the ideological importance of such metaphor framing techniques, and the common speculation that climate anxieties are being displaced onto new forms of anti-immigrant racism. Contextualizing the reports against a broader history of deploying metaphors of 'abject nature' in xenophobic and racist discourse, the article traces the outline of an emergent politics of abjection shaped by historically specific constructions of both race and nature.